The effect of blended teaching strategies on the acquisition of historical concepts by social science students - خالید, أ.م.د حسن فخر الدين خالد; Asst,L. .Soran Hama Amin Ahmad Mala Mala (Sulaimani Journal for Humanities, 2025)
The aim of this study is to determine the effect of blended teaching strategy on the acquisition of historical concepts by third year students of the Department of Social Sciences- College of Basic Education- University of Sulaimani. To achieve the study objective, the empirical method was used. The study population consists of 79 students. A sample of 60 students was selected and divided into two groups, with 30 students in the control group to study the subject traditionally and 30 students in the experimental group to study the topic with blended teaching strategy; The study sample is also matched according to the variable of age, and IQ. Moreover, a 60-item test concerning historical concepts is set in three-question styles. After collecting data and statistical analysis, the results show that there is a significant statistical difference between the average scores of students in the experimental group and the control group. Which (4.080) is greater than the tabulated value, which is (1.96), and with a degree of freedom (58), at the level of evidence (0.05)) and (where the calculated value (T) is equal to (10.410, the tabular value is equal to (96.1) and the degree of freedom). (58) At the level of evidence (05.0) Finally, the study concluded that blended learning strategies have a significant positive effect on the acquisition of historical concepts among the students of Social Sciences Department. The study also suggests that the teachers of history in the Department of Social Sciences of the College of Basic Education should pay more attention to blended learning strategies, because in addition to its importance, it is also a reason to prepare students and teachers for any unwanted situations that disrupt classroom learning.
Keywords: Blended teaching learning; historical concepts; strategies